Nutrient availability and limitation within soils of polygonal tundra in the Sakha Republic, Russian Federation - Beermann, Fabian (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2016)
The presented study was conducted to get a comprehensive overview on limiting and available nutrients in the soil-vegetation system of arctic polygonal tundra landscapes and to give an outlook into the future state of nutrient limitation in this ecosystem in the course of climate change. The objectives of this study were in detail: (1) To analyze availability and limitation of nutrients in the soil-vegetation system of an arctic polygonal tundra landscape, (2) to quantify pools of inorganic nitrogen within the perennially frozen ground and the active layer of different soils in the Siberian arctic, (3) to give an estimate of potential annual nitrogen release rates in the course of climate change, and (4) to assess the changes of microbial growth, microbial respiration and nitrogen availability in arctic soils in response to increased temperatures by a soil incubation study. Three different sites in the Eastern Siberian arctic were investigated in this study. The westernmost study site was located in the Lena River Delta The second study area was located in the Indigirka and the third and easternmost study area was located in the Kolyma River Delta. All three study areas were located in the Siberian zone of continuous permafrost and were characterized by polygonal tundra. Limiting and available nutrients in the polygonal tundra in the Indigirka Lowlands were analyzed by a stoichiometric approach, based on the N/P ratios in the vegetation biomass, the microbial biomass, the pools of inorganic and organic nutrients and the total elemental pools. Eleven soil profiles down to one meter depth below surface at the three different study areas were studied to quantify pools of inorganic nitrogen in arctic permafrost-affected soils. Furthermore, the potential thickening of the seasonally unfrozen soil layer under higher temperatures for the three study areas was modeled to estimate potential annual nitrogen mobilization from thawing permafrost. In addition, soil samples of one soil profile from the study area in the ...